2018
DOI: 10.22540/jfsf-03-105
|View full text |Cite
|
Sign up to set email alerts
|

Enablers and barriers to older people’s participation in strength and balance activities: A review of reviews

Abstract: Encouraging physical activity is a key aspect of public health, with links to significant health benefits, including reducing the risk of a range of diseases, e.g. coronary heart disease, stroke, type 2 diabetes, and helping to maintain a healthy weight 1,2. The UK Chief Medical Officers' (CMOs) guidelines for physical activity present evidence-based, age-specific recommendation for physical activity to improve public health 3. Alongside recommendations for aerobic physical activity (150 minutes per week of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
45
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 20 publications
6
45
0
9
Order By: Relevance
“…Social aspects related to physical activity were also more important for moderately to vigorously physically active older women than for inactive older women, but in older men, there was no difference in this motivational factor. Comparisons of our findings with those of previous systematic reviews evaluating older individuals' motives for physical activity 9,10 reveal that physical and psychological health and well-being, as well as enjoyment, seem to be major and universal motivational factors to be physically active in older individuals. Previous studies have also indicated the social aspects of physical activity as important motivational factors, but we could not confirm this result in the present study.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…Social aspects related to physical activity were also more important for moderately to vigorously physically active older women than for inactive older women, but in older men, there was no difference in this motivational factor. Comparisons of our findings with those of previous systematic reviews evaluating older individuals' motives for physical activity 9,10 reveal that physical and psychological health and well-being, as well as enjoyment, seem to be major and universal motivational factors to be physically active in older individuals. Previous studies have also indicated the social aspects of physical activity as important motivational factors, but we could not confirm this result in the present study.…”
supporting
confidence: 62%
“…Furthermore, we examine to what extent genetic and environmental factors contribute to motives for physical activity. Based on previous studies, 9,10 we hypothesize that both physical health and psychological health along with enjoyment of physical activity are the most important factors to induce both older men and women to be physically active. Further, based on previous findings, 6,11 we hypothesize that there are sex differences in motives for physical activity among older individuals-older women are assumed to be more likely motivated by their appearance and the social aspect of physical activity than older men.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Adherence to home-based interventions for falls prevention can be low and may be influenced by programme characteristics and the amount of support provided 7 . The social interaction that comes from group exercise interventions is highly valued by older adults 8 and facilitates acceptability 9 . It is possible that blended programmes, which combine intermittent group sessions (i.e.…”
mentioning
confidence: 99%